THE DICTIONARY OF MODERN PROVERBS: THIRD SUPPLEMENT - Doyle, Charles Clay; Mieder, Wolfgang (Proverbium - Yearbook, 2020)
This is the third supplement to The Dictionary of Modern Proverbs (New Haven, Connecticut: Yale University Press, 2012), edited by Charles Clay Doyle, Wolfgang Mieder, and Fred R. Shapiro. It registers 53 additional modern Anglo-American proverbs with historical dates and contextualized references. We intend to publish such supplements from time to time and hope eventually to bring out a new edition of our dictionary.